Teachers' Strategies In Teaching English Vocabulary At Wca Cruise Ship Hospitality and Culinary Training Center Jakarta - Edri, Edri (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2025)
Emphasizing vocabulary teaching is a very efficient approach to improve students' English comprehension. Vocabulary is the foundation for constructing meaningful and grammatically accurate sentences, emphasizing vocabulary teaching is a very efficient approach to improve students' English comprehension. Students sometimes struggle to comprehend reading materials, express their thoughts, and participate in classroom debates without a strong language foundation. Therefore, vocabulary teaching should be relevant, interesting, and tailored to students' needs and should not be limited to rote learning of word lists. A studyWCA Training Cruise Jakarta Schoollooked at how teachers approach language teaching and how different approaches affect students. The study found that lack of vocabulary is a significant barrier to student learning through interviews, surveys, and document analysis. The teachers used several techniques—including games, translation, media, pantomime, and physical activity—to make learning more engaging and efficient in response. These techniques made the learning experience more enjoyable and helped students remember new terms more easily. The study found that efficient vocabulary teaching requires different, student-centered strategies that encourage